Les Méta-Barons, des cyborgs subversifs ? - Adrien Cascarino (ReS Futurae, 2019)
In recent years, there has been an increasing overlap between science fiction and scientific narratives, particularly with the rise of transhumanism, a movement advocating the use of science and technology to improve human physical and mental capacities. These discourses are often criticized as shifting towards hubris, contempt for the body, or even denial of death and finiteness. In this context, what representations of the transhuman bodies does the francophone comic strip offer? Are they representations of "augmented", divine and limitless bodies? Or do these representations, on the contrary, aim to denounce an hubris underlying this lust for augmentation?To answer this question, this article focuses on the representation of transhuman bodies in La Caste des Méta-Barons, an 8-volume comic strip series written by Alejandro Jodorowsky, drawn by Juan Gimenez and published between 1992 and 2003.The study of this comic strip, contemporary with the beginnings of the transhumanist movement, but above all with the emergence of an ambivalent figure of the cyborg (Haraway, 1984), highlights a certain representation of the posthuman body, which pre-dates current developments on the question.Through the study of the narrative and graphic structure of these albums, this article shows that contrary to appearances, the transhuman bodies of the meta-barons, both cyborg and hybrid, are moving away from the ideal of a divine and all-powerful body and on the contrary blur the line between the augmented body and the disabled body, showing that any physical modification is accompanied by a loss, access to a truly augmented body then passing through the acceptance of this loss.